Food System Digitalization as a Means to Promote Food and Nutrition Security in the Barents Region - Raheem, Dele; Shishaev, Maxim; Dikovitsky, Vladimir (Agriculture, 2019)
The consumption of food and its safety are important for human security. In this paper, we reviewed the literature on future possibilities for transforming the food system through digital solutions in the Barents region. Such digital solutions will make food business operators more eﬃcient, sustainable, and transparent. Developing cross-border infrastructures for digitalization in the region will break the isolation of the local food system, thus simplifying the availability of processed, novel and safe traditional food products. It is necessary for food growers and processors to respond to the trends driven by consumers’ demand while ensuring their safety. Our review highlights the opportunities provided by digital technology to ensure safety and help food business operators predict consumer trends in the future. In addition, digitalization can create conditions that are necessary for the diversification of organizational schemes and the eﬀective monitoring of food processing operations that will help to promote food and nutrition security in the Barents region.